Investigation on early autonomous vehicle manoeuvre information to motion sickness symptoms using road test method - Sulaiman, Mohammad Izhar (2024)
The development of autonomous vehicles has been started by various automakers. Once available for the masses, this technology allows all passengers to engage in non-driving related activities, such as reading books, watching movies, and playing video games, as studied in various countries before, except for Malaysian passengers. One of the concerning issues regarding the benefits is the development of motion sickness. It is a type of sickness that exists among passengers of various transportation, with an increased chance of getting the symptoms when they remove the focus from the vehicle’s trajectory. Hence, this thesis was completed to determine the severity of motion sickness based on the vehicle’s motion (predictable and unpredictable motion) and to develop prototypes that can reduce motion sickness symptoms among autonomous vehicle users while engaging in non-driving related activities. In addition, the most preferred non-driving related activities among Malaysian passengers were also studied to fill the gap in the study. The motion sickness studies were performed in a real-road environment with controlled conditions using an instrumented vehicle as the real-road autonomous vehicle simulator. On the other hand, the preferred non-driving related activities among Malaysians were conducted by distributing an online questionnaire over six months. The results showed that the unpredictable motion induced higher motion sickness compared to the predictable motion. Furthermore, the top three non-driving related activities that were preferred among Malaysian passengers were found to be “listening to music”, “interacting with others”, and “calling and texting”. The developed prototypes using audio and visual modalities that were tested on real-road were able to supply the early trajectory of the vehicle to the passengers, hence improving their situation awareness. The ability to predict the vehicle’s trajectory contributes towards mitigating motion sickness levels. This thesis shows that the information on the vehicle’s trajectories is important for the passengers, especially when their focus is removed while engaging in non-driving related activities. In addition, automakers should consider embedding tested prototypes that increase passengers’ situation awareness to minimise motion sickness symptoms. Meanwhile, the completed data on the preferred non-driving related activities can be a guideline for autonomous vehicle production that is suitable for potential Malaysian users.